(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
COVID-19, also known as coronavirus disease 2019, is a viral respiratory illness caused by the SARS-CoV-2 virus. It emerged in late 2019 and has since become a global pandemic. On the other hand, chronic hepatitis C is a liver disease caused by the hepatitis C virus (HCV), which can lead to long-term liver damage and other complications if left untreated.